2009
DOI: 10.1586/ern.09.9
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of oncolytic HSV vectors for glioblastoma therapy

Abstract: Glioblastoma multiforme is one of the most common human brain tumors. The tumor is generally highly infiltrative, making it extremely difficult to treat by surgical resection or radiotherapy. This feature contributes to recurrence and a very poor prognosis. Few anticancer drugs have been shown to alter rapid tumor growth and none are ultimately effective. Oncolytic vectors have been employed as a treatment alternative based on the ability to tailor virus replication to tumor cells. The human neurotropic herpes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 109 publications
(98 reference statements)
0
34
0
Order By: Relevance
“…7 Therefore, subsequent developments of HSV-1-based glioma therapy have focused on ways to enhance antitumor efficacy. 8 Two main strategies have been followed: modifying the vectors by deleting the immunoattenuating genes coded for by the virus, to allow enhanced immunorecognition of vector-infected cells, 9 or, by inserting immunostimulatory or therapeutic transgenes, [10][11][12][13] as well as by combining the vectors with other clinical treatment forms such as chemotherapy 14 or irradiation. 15 In neuro-oncology, the validity of experimental data obtained from preclinical evaluation of potential clinical therapies has been compromised by the widespread use of tumor-cell-line-based animal models.…”
Section: Introductionmentioning
confidence: 99%
“…7 Therefore, subsequent developments of HSV-1-based glioma therapy have focused on ways to enhance antitumor efficacy. 8 Two main strategies have been followed: modifying the vectors by deleting the immunoattenuating genes coded for by the virus, to allow enhanced immunorecognition of vector-infected cells, 9 or, by inserting immunostimulatory or therapeutic transgenes, [10][11][12][13] as well as by combining the vectors with other clinical treatment forms such as chemotherapy 14 or irradiation. 15 In neuro-oncology, the validity of experimental data obtained from preclinical evaluation of potential clinical therapies has been compromised by the widespread use of tumor-cell-line-based animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of safe, selectively replication-competent viruses has been predominantly accomplished by disruption of the HSV virulence factor ICP34.5 (1,2). Several such viruses have been used in clinical trials (3,4) and have demonstrated efficacy in preclinical studies (5).…”
mentioning
confidence: 99%
“…Accordingly, secondgeneration viruses are being developed. These combine the oncolytic activity and safety of the first-generation HSV-1 mutants with the delivery of tumoricidal transgenes (2,4,5). Because of the difficulty in targeting every cell within a tumor, either for oncolysis or for transgene delivery, a successful cancer gene therapy strategy will mediate killing of infected and noninfected bystander tumor cells.…”
mentioning
confidence: 99%
“…This specificity is particularly required when designing therapies for brain tumors, such as glioblastoma multiforme (GBM), in which tumor cells infiltrate the normal brain. GBM is the most common primary brain cancer in adults, and carries a dismal prognosis (14-to 21-mo median survival), in spite of an advanced standard of care, namely surgery, radiotherapy, and chemotherapy with temozolomide (6)(7)(8).…”
mentioning
confidence: 99%